Caregiver insights on challenges and needs in fecal incontinence products: a mixed methods study - Yu, Lanlan; Hao, Fengming; Li, Jie; Hu, Yingjie; Xiong, Fei; Chen, Ling; Cai, Wenzhi (Frontiers in Public Health, 2025)
AimsThis study explores the real–world use and challenges of fecal incontinence (FI) collection products—both absorbent items (pads, diapers) and dedicated fecal-collection devices with adhesive fixators—among long-term, bed-bound hospital patients, while also considering broader public-health implications. It seeks to identify barriers to optimal product use and to offer recommendations for improving incontinence management outcomes.BackgroundEffective FI management is essential to patient wellbeing and to preventing healthcare-associated infections (HAIs). Although multiple FI collection products are available, their use in long-term hospital settings remains suboptimal, largely because of caregiver training gaps and limited resources.MethodsThis mixed-methods study used an explanatory sequential design. Quantitative data were gathered through online and paper-based surveys administered to caregivers in three hospitals (n = 318). These data were supplemented by qualitative interviews (n = 24) that provided deeper insight into the challenges identified. We performed descriptive and inferential statistical analyses, including logistic regression, and carried out a thematic analysis of interview transcripts to clarify the factors influencing product choice and the related public-health implications.ResultsProduct choice was shaped by distinct factors across caregiver groups. For family caregivers, household income (OR = 2.380) and living arrangement (OR = 0.344) were major determinants. Among nursing assistants, prior training (OR = 8.817) strongly affected selection. For nurses, incontinence-associated dermatitis training (OR = 3.344) and work environment (OR = 3.304) were critical. Qualitative interviews highlighted mismatches between available products and actual needs, emphasizing the importance of reforming procurement channels, raising awareness, and tailoring caregiver education.ConclusionsDisparities in FI product use stem mainly from economic constraints, training gaps, and limited awareness. Enhancing caregiver training, streamlining product distribution, and broadening insurance support could strengthen FI management and reduce HAIs. Although the findings offer useful guidance for policy and practice, their generalizability is limited by the single geographic setting and reliance on self-reported data. Future studies should examine diverse institutional contexts to validate and extend these results.